Autoimmune Abnormalities of Postpartum Thyroid Diseases - Di Bari, Flavia; Granese, Roberta; Le Donne, Maria; Vita, Roberto; Benvenga, Salvatore (Frontiers in Endocrinology, 2017)
The year following parturition is a critical time for the de novo appearance or exacerbation of autoimmune diseases, including autoimmune thyroid disease. The vast majority of postpartum thyroid disease (PPTD) consists of postpartum thyroiditis (PPT) and the minority by Graves’ disease and nonautoimmune thyroiditis. PPT has a worldwide prevalence ranging from 1% to 22% and averaging 5% based on a review published in 2012. Several factors confer risk for the development of PPT. Tipically, the clinical course of PPT is characterized by three phases: thyrotoxic, hypothyroid and euthyroid phase. Approximately half of PPT women will have permanent hypothyroidism. The best humoral marker for predictivity, already during the first trimester of gestation, is considered positivity for thyroperoxidase autoantibodies (TPOAb), though only one-third to half of such TPOAb-positive pregnant women will develop PPT. Nutraceuticals (such as selenium) or omega-3-fatty acid supplements seem to have a role in prevention of PPT. In a recent study on pregnant women with stable dietary habits, we found that the fish-consumers had lower rates of positivity (and lower serum levels) of both TPOAb and thyroglobulin Ab (TgAb) compared to meat-eaters. Finally, we remind the reader of other diseases that can be observed in the postpartum period, either autoimmune or nonautoimmune, thyroid or nonthyroid.